Pharmacokinetics of Arctigenin and Fructus Arctii Powder in Piglets - He, Bin; Zhang, Hai-Jing; Yang, Wen-Hai; Shao, Zhi-Yong; Wu, Li-Jun; Chen, Xia-Bing; Chen, Jie; Liu, Wu; Ran, Zhi-Ping; Jin, Rr-Guang; Cao, Ji-Yue (Frontiers in Veterinary Science, 2019)
Fructus arctii is also called great power seed，which is the dried fruit of the Arctium lappa in Compositae, Is a common veterinary herbal medicine, Arctigenin is its direct active ingredient. The aim of the study was to understand the absorption, distribution, metabolism, and excretion of arctigenin and Fructus arctii powder in piglets, to provide a theoretical reference for the development and clinical use of new veterinary drugs. Sixteen healthy piglets (mean weight, 30.0 ± 5.0 kg) were selected and divided into two groups. One group was administered 2.0 mg/kg.bw arctigenin intravenously, and the other group was administered 1.0 g/kg.bw Fructus arctii powder by gavage. Blood samples were collected from the anterior vena cava at different time points, and the concentration of arctigenin in the plasma of the piglets was analyzed by high-performance liquid chromatography. Arctigenin conformed to the two-compartment model with no absorption, and the main pharmacokinetic parameters were: distribution half-life (t1/2α)—0.166 ± 0.022 h; elimination half-life (t1/2β)—3.161 ± 0.296 h; apparent volume of distribution (Vd)—0.231 ± 0.033 L/kg; clearance rate (CLb)—0.057 ± 0.003 L/(h.kg); and the area under the curve (AUC)—1.189 ± 0.057 g.h/mL. The main pharmacokinetic parameters of arctigenin following the oral administration of the Fructus arctii powder were as follows: the absorption half-life (t1/2ka)—0.274 ± 0.102 h, t1/2α—1.435 ± 0.725 h, t1/2β—63.467 ± 29.115 h, Vd—1.680 ± 0.402 L/kg, CLb—0.076 ± 0.028 L/(h.kg), peak time (tmax)—0.853 ± 0.211 h, peak concentration (Cmax)—0.430 ± 0.035 g/mL, and AUC—14.672 ± 4.813 g/mL. These results indicate that intravenously injected arctigenin were less distributed in the tissues and were rapidly eliminated from blood of the piglets; however, orally administered Fructus arctii powder exhibited rapid absorption, more distribution, and slower elimination, which could result in sustained pharmacological effects.